1978
DOI: 10.1039/f19787401758
|View full text |Cite
|
Sign up to set email alerts
|

Ionic activities in sodium dodecyl sulphate solutions from electromotive force measurements

Abstract: Measured surfactant ion activities (al) and counterion activities (az) in solutions of sodium dodecyl sulphate (SDS) in the presence and absence of NaCl are reported. The results show that premicellar association is insignificant. Mean ionic activities of surfactant (a&) above the c.m.c. (critical micelle concentration) agree well with estimates from light scattering. This shows that the surfactant ion electrodes work well in the presence of micelles and that solubilisation of membrane constituents is unimport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 0 publications
3
73
1
Order By: Relevance
“…4 (circles), remains close to zero up to the CMC and then increases linearly with added lipid shortly thereafter. Electrode measurements with anionic surfactants have revealed that the monomer activity begins to decrease with increasing surfactant concentration above the CMC, because of the increasing micelle concentration (12)(13)(14). If this also happens with (8:0) 2 PG, it does not appear to be associated with an appreciable heat evolution or absorption (see Fig.…”
Section: Thermodynamics Of Demicellizationmentioning
confidence: 90%
“…4 (circles), remains close to zero up to the CMC and then increases linearly with added lipid shortly thereafter. Electrode measurements with anionic surfactants have revealed that the monomer activity begins to decrease with increasing surfactant concentration above the CMC, because of the increasing micelle concentration (12)(13)(14). If this also happens with (8:0) 2 PG, it does not appear to be associated with an appreciable heat evolution or absorption (see Fig.…”
Section: Thermodynamics Of Demicellizationmentioning
confidence: 90%
“…The first becomes larger and larger and at a higher rate with a decreasing value of ␤ (␤ Ͻ 1). So, the relation [5] can be written as…”
Section: Figmentioning
confidence: 99%
“…Electromotive force (EMF) measurements usually allow access, on the one hand, to one of the main typical features of ionic micelles, the effective association rate ␤, and on the other hand, to interesting information comparing EMF measurements with amphiphile and counterion-selective electrodes (1,2,5,8,(13)(14)(15). By means of the electrochemical method (16 -18) the determination of the ␤ value for different surfactants and counterions is now accurate and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Free energies of micellar systems can readily be measured from colligative properties (7,9) or from electromotive forces (29)(30)(31). Then, from the experimental free energies and enthalpies, the partial molal entropies of the surfactant solutions can also be calculated as a function of concentration (6).…”
Section: = (+Cm)/mmentioning
confidence: 99%